Filling the Gap : Digital Credit and Financial Inclusion - Bazarbash, Majid (IMF Working Papers; Working Paper ;, 2020)
Can fintech credit fill the credit gap in the consumer and business segments? There are few cross-country studies that explore this question. Focusing on marketplace lending, an important part of fintech credit, we use data for 109 countries from 2015 to 2017 to study the relationship between fintech credit to businesses and consumers and various aspects of financial development. Marketplace lending to consumers grows in countries where financial depth declines highlighting the role of fintech credit in filling the credit gap by traditional lenders. This result is particularly strong in low-income countries. In the business segment, marketplace lending expands where financial efficiency declines. Our findings show that low-income countries take advantage of the fintech credit opportunity in the consumer segment but face important challenges in the business segment.